The Effects of Gavage Extract of Papaver Rhoeas L on Blood Pressure of MIA Induced Osteoarthritis and Its Interaction with Nitrergic System in male Rat - Sareh Sangy; Faeghe Miryousefiata; Aminollah Bahaoddini; Herlina Dimiati (Budapest International Research and Critics University, 2020)
Hypertension is one of the most common and most prevalent diseases in the world today. Chronic inflammation is one of the risk factors for cardiovascular disease (CVD). Since synovial inflammation plays a role in the initial stages of osteoarthritis (OA), therefore, the side effects of OA are the incidence of CVD. One of the most appropriate methods for treating this disease is the use of medicinal herbs that have a blood pressure modifying effect Due to OA as Papaver rhoeas. The present research shows The Effects of Extract of Papaver rhoeas on Blood Pressure of rats with OA and Its Interaction with nitrergic System. OA model in 35 male rats was created by injection of monosodium iodoacetate (MIA) into the right knee joint and then were gavaged with extract of Papaver rhoeas for 30 days. On day 30, the veins and arteries of the animal were then cannulated for injection and measurement of blood pressure, respectively. Blood pressure parameters (systolic, diastolic, mean arterial pressure) were recorded in groups before and after L-NAME injection. The results were analyzed using SPSS software. Systolic, diastolic, and mean arterial pressure in response to extract of Papaver rhoeas was reduced compared to control(OA), as well as Significant decrease in systolic and diastolic pressure and mean arterial pressure and increased heart beat rate in the presence of extract and LNAME as compared with control group. (P <0/05) .We found that the aqueous extract of Papaver rhoeas has a decreasing effect on blood pressure in rats with OA. This effect may be due to inhibition of the nitrergic system.